The American slave narrative and the Victorian novel - Lee, Julia Sun-Joo, 1976- (New York ; Oxford : Oxford University Press, 2010)
This title explores the influence of the American slave narrative on the Victorian novel. The book argues that Charlotte Bronte, Charles Dickens, and Robert Louis Stevenson integrated into their works elements of the slave narrative.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English fiction -- 19th century -- History and criticism; English literature -- American influences; Slave narratives